Introduction to information systems - Rainer, R. Kelly; Prince, Brad (John Wiley & Sons, 2017)
The theme of this book is What's In IT for Me? This question is asked by all students who take this course. The book will show you that IT is the backbone of any business, whether a student is majoring in Accounting, Finance, Marketing, Human Resources, or Production/Operations Management.